2002
DOI: 10.1083/jcb.200110007
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-mediated cleavage of the stacking protein GRASP65 is required for Golgi fragmentation during apoptosis

Abstract: he mammalian Golgi complex is comprised of a ribbon of stacked cisternal membranes often located in the pericentriolar region of the cell. Here, we report that during apoptosis the Golgi ribbon is fragmented into dispersed clusters of tubulo-vesicular membranes. We have found that fragmentation is caspase dependent and identified GRASP65 (Golgi reassembly and stacking protein of 65 kD) as a novel caspase substrate. GRASP65 is cleaved T specifically by caspase-3 at conserved sites in its membrane distal COOH te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
217
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(231 citation statements)
references
References 41 publications
(59 reference statements)
11
217
0
3
Order By: Relevance
“…A number of secretory pathway proteins are substrates for caspase cleavage, including BAP-31 in the ER (Ng et al, 1997), and golgin-160 (Mancini et al, 2000), giantin (Lowe et al, 2004), GRASP65 (Lane et al, 2002), and p115 (Chiu et al, 2002) at the Golgi. Besides contributing to organelle disassembly, cleavage of some of these proteins seems to be important for initiation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of secretory pathway proteins are substrates for caspase cleavage, including BAP-31 in the ER (Ng et al, 1997), and golgin-160 (Mancini et al, 2000), giantin (Lowe et al, 2004), GRASP65 (Lane et al, 2002), and p115 (Chiu et al, 2002) at the Golgi. Besides contributing to organelle disassembly, cleavage of some of these proteins seems to be important for initiation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas elements of mitotic and apoptotic Golgi disassembly seem to have features in common (Sesso et al, 1999), apoptotic Golgi disassembly is irreversible and primarily depends on protein cleavage rather than phosphorylation. During apoptosis, caspases cleave proteins involved in Golgi structure and trafficking, including golgin-160 (Mancini et al, 2000), GM130 (Nozawa et al, 2002;Lowe et al, 2004), giantin (Lowe et al, 2004), GRASP65 (Lane et al, 2002), and p115 (Chiu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to note that in apoptotic cells, the NH 2 -terminal head domain of GCP170 was cleaved by caspases, whereas a mutant form of GCP170 lacking the caspase-2 cleavage site appeared to delay the Golgi fragmentation (26). In addition, Lane et al (49) most recently reported that the stacking protein GRASP65 was also cleaved by caspase-3 during apoptosis, resulting in Golgi fragmentation. These observations strongly suggest that GCP170 and GRASP65 of the golgin family are indeed required for the assembly and maintenance of the Golgi structure.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this possibility, it has been demonstrated that stress in ER can induce apoptosis (Welihinda et al 1999), at least through Ca 2 ϩ release and the activation of caspase-12 (Nakagawa et al 2000). In addi- tion, Golgi disruption has been described in apoptosisinduced HeLa cells through activation of caspase-2 (Mancini et al 2000) and caspase-3, as recently reported (Lane et al 2002). We conclude that Golgi modifications found in a rat OA-induced model matches cartilage damage progression and we speculate that they might be related to chondrocyte death by apoptosis, first increasing synthesis and finally implicated in chondrocytes fragmentation.…”
Section: Discussionmentioning
confidence: 78%